Conjugated Cobalt Polyphthalocyanine as the Elastic and Reprocessable Catalyst for Flexible Li–CO2 Batteries. Issue 2 (4th November 2018) - Chen, Junmei; Zou, Kaiyi; Ding, Pan; Deng, Jun; Zha, Chenyang; Hu, Yongpan; Zhao, Xuan; Wu, Jialing; Fan, Jian; Li, Yanguang
Abstract: Li–CO2 batteries represent an attractive solution for electrochemical energy storage by utilizing atmospheric CO2 as the energy carrier. However, their practical viability critically depends on the development of efficient and low‐cost cathode catalysts for the reversible formation and decomposition of Li2 CO3 . Here, the great potential of a structurally engineered polymer is demonstrated as the cathode catalyst for rechargeable Li–CO2 batteries. Conjugated cobalt polyphthalocyanine is prepared via a facile microwave heating method. Due to the crosslinked network, it is intrinsically elastic and has improved chemical, physical, and mechanical stability. Electrochemical measurements show that cobalt polyphthalocyanine facilitates the reversible formation and decomposition of Li2 CO3, and therefore enables high‐performance Li–CO2 batteries with large areal capacity and impressive cycling performance. In addition, the elastic and reprocessable property of the polymeric catalyst renders it possible to fabricate flexible batteries. Abstract : Conjugated cobalt polyphthalocyanine facilitates the reversible formation and decomposition of Li2 CO3, and enables flexible Li–CO2 batteries with large areal capacity and impressive cycle life.